PENGARUH LAMA USAHA, KELENGKAPAN BARANG, MODAL DAN OMSET PENJUALAN TERHADAP PENDAPATAN WARUNG TRADISONAL DI PAYANGAN - Prawira, Ida Bagus Gaga Yudi; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 11 (2020): VOL 9 NO 11, NOVEMBER 2020 (2390 - 2617), 2020)
Traditional traders in Payangan sub-district who compete with a number of minimarkets in Payangan sub-district, this raises the problem of the difficulty of traditional stalls surviving in the midst of many modern markets or minimarkets in many places, especially in Payangan sub-district. The sample in this study used the Cochran formula with a total of 96 stall traders in Payangan District. This research uses interaction analysis analytical techniques or Moderated Regression Analysis. The results of this study concluded that the length of business, completeness of goods, capital, and sales turnover simultaneously had a significant effect on the income of traditional warung traders in Payangan District. The length of time the business is partially positive and not significant effect, the completeness of the goods partially has a positive and significant effect, the capital partially has a positive and significant effect, the sales turnover moderates which strengthens the relationship between capital on traditional stall income in Payangan District.   Keywords: traditional traders, length of business, completeness of goods, capital, sales turnover, merchant income